An Amazonian Dream on the Ecuadorian Coast: The alternative economy of the Shuar Tsuer Entsa tourist center - Wajai Mashu, Julio; Kitiar, Rosalía (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
The Tsuer Entsa initiative serves as a model of alternative economics and Shuar cultural resistance on Ecuador’s coast. Through self-managed tourism, the community is rebuilding its Amazonian identity, prioritizing the transmission of traditional knowledge and financial autonomy in the face of limited government intervention. This project transforms heritage into a political resource that ensures social cohesion and the survival of the ancestral worldview in the face of the logic of globalization.